The false trade‐off of relevance for safety in children's search systems. Issue 1 (18th October 2019) - Figueiredo, Vanessa; Meyers, Eric M.
ABSTRACT: Since the wide adoption of the Internet in public schools and libraries, parents, educators and caregivers have been concerned about the safety and efficacy of children's search practice, often willing to accept diminished information quality to ensure that young searchers do not encounter illicit materials. In this study, part of a broader examination of youth search practices in the early years, we demonstrate that "safe", child‐oriented search engines provide less relevant results, while failing to keep children from the unfiltered Web, the narrow definition of safety proffered by the sites themselves. Based on our findings, we suggest that the rhetorics of these search tools present a false trade‐off and may actually hinder inquiry practice, as opposed to supporting safe and developmentally appropriate access to online materials.